Agricultura Urbana e a transformação da vida e da paisagem no Tatuquara, Curitiba-PR - Valéria Borges Yonegura; Henrique Manoel da Silva (Confins)
Urban agriculture (UA) is characterized by agricultural production within urban and peri-urban areas to produce food or generate income. Depending on the context of the place where it is implemented, this practice can improve the landscape, the quality of life and food of producers, as well as their social relations. This paper aims to present visible transformations, not only of the environment, but also the improvement of the quality of life of urban farmers in Tatuquara, at Curitiba-PR, during the years 2017 and 2018. It was observed that UA was responsible for increasing the improvement of life, landscape and security in the local community, as well as the sense of topophilia, the emotional bond between people and place, according to Yi-Fu Tuan. Despite its use in urban marketing, the continuity of the practice is threatened by the possible end of the partnership with the power utility and by pressure from the real estate market. For this paper, a literature review on the concept of UA was conducted, as well as a historical-geographical study of the neighborhood in question. Interviews with urban farmers at Tatuquara were conducted to assess their feelings about UA and how this practice has affected their lives.